Pemanfaatan Pojok Baca dalam Menumbuhkan Minat Baca di SDIT Madani Islamic School Payakumbuh - David, David; Sari, Tika Purnama (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This research aims to analyze the benefits of reading corners in fostering interest in reading which has been programmed at SD IT Madani Islamic School! Payakumbuh. The research method used is qualitative with a descriptive approach. Data collection techniques use observation. The data analysis technique was carried out descriptively by looking at the results of observations. Based on the results of data analysis, it can be concluded that the use of the reading corner for SD IT Madani Islamic School Payakaumbuh students is that there is a reading corner in the library room in order to bring sources of knowledge closer to students and can foster basic literacy. This research was conducted directly and the results of the findings of interest in writing in the use of the reading corner at SD IT Madani Islamic School Payakumbuh were that students were able to create new vocabulary into sentences. The results of this research can be concluded that after utilizing the interest in reading and writing at SD IT Madani Islamic School Payakumbuh, it is very important and helps students and teachers in adding new vocabulary and new knowledge. By creating an innovative reading corner, it can increase students' interest in reading at SD IT Madani Islamic School Payakumbuh.